Redesain stasiun kerja untuk pembuatan kain batik tulis - Moch. Junaidi Hidayat; Nurul Ulfa (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
Batik belongs to an Indonesian cultural heritage that has spread throughout the archipelago and produces various motifs displaying the characteristics of each region. Compared to other types of batik, written batik requires more patience and perseverance during the manufacturing process. The results of surveys conducted on five hand-drawn batik craftsmen in Samarinda, namely D'Five, Batik Putri Syafril, LKP Atiiqna, Lilis Batik, and Borneo Craft Indonesia, indicated that even though the times have been modern, the process of batik making still uses things at home without paying attention to convenience while doing batik activities. The design of this workstation aims to facilitate batik activities, especially at the stage of tracing the motifs onto the fabric and embroidering. The redesign of this batik workstation employed a design analysis by considering the needs, activities, systems, ergonomics, anthropometry, placement, materials, and colors through a qualitative method. This sort of method was carried out by observing problems directly at the location, conducting interviews with craftsmen, and documenting the tools used. The result of this research is the compilation of a workstation design prototype having a modern design style that highlights the functionality of the product. It focused on the process of tracing batik motifs from paper onto cloth and proceeding to the imprinting process, which can be done at one workstation. It presents the features of a tracing area that can be tilted according to tracing needs, the integration of a lightbox, and a focus lamp that can be turned on at any time, as well as innovations in cloth rollers and webbing to ease the cloth pulling and rolling.